Hypoxia-Mediated Complement 1q Binding Protein Regulates Metastasis and Chemoresistance in Triple-Negative Breast Cancer and Modulates the PKC-NF-κB-VCAM-1 Signaling Pathway - Wu, Hao; Chu, Yijun; Sun, Shanshan; Li, Guozheng; Xu, Shouping; Zhang, Xianyu; Jiang, Yongdong; Gao, Song; Wang, Qin; Zhang, Jian; Pang, Da (Frontiers in Cell and Developmental Biology, 2021)
Objectives Complement 1q binding protein (C1QBP/HABP1/p32/gC1qR) has been found to be overexpressed in triple-negative breast cancer (TNBC). However, the underlying mechanisms of high C1QBP expression and its role in TNBC remain largely unclear. Hypoxia is a tumor-associated microenvironment that promotes metastasis and paclitaxel (PTX) chemoresistance in tumor cells. In this study, we aimed to assess C1QBP expression and explore its role in hypoxia-related metastasis and chemoresistance in TNBC. Materials and Methods RNA-sequencing of TNBC cells under hypoxia was performed to identify C1QBP. The effect of hypoxia inducible factor 1 subunit alpha (HIF-1α) on C1QBP expression was investigated using chromatin immunoprecipitation (ChIP) assay. The role of C1QBP in mediating metastasis, chemoresistance to PTX, and regulation of metastasis-linked vascular cell adhesion molecule 1 (VCAM-1) expression were studied using in vitro and in vivo experiments. Clinical tissue microarrays were used to verify the correlation of C1QBP with the expression of HIF-1α, VCAM-1, and RELA proto-oncogene nuclear factor-kappa B subunit (P65). Results We found that hypoxia-induced HIF-1α upregulated C1QBP. The inhibition of C1QBP notably blocked metastasis of TNBC cells and increased their sensitivity to PTX under hypoxic conditions. Depletion of C1QBP decreased VCAM-1 expression by reducing the amount of P65 in the nucleus and suppressed the activation of hypoxia-induced protein kinase C-nuclear factor-kappa B (PKC-NF-κB) signaling. immunohistochemistry (IHC) staining of the tissue microarray showed positive correlations between the C1QBP level and those of HIF-1α, P65, and VCAM-1. Conclusion Targeting C1QBP along with PTX treatment might be a potential treatment for TNBC patients.